2020
DOI: 10.1007/s00248-020-01628-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Niche Differentiation in the Environmental Responses of Co-occurring Mucoromycotinian Fine Root Endophytes and Glomeromycotinian Arbuscular Mycorrhizal Fungi

Abstract: Fine root endophytes (FRE) were traditionally considered a morphotype of arbuscular mycorrhizal fungi (AMF), but recent genetic studies demonstrate that FRE belong within the subphylum Mucoromycotina, rather than in the subphylum Glomeromycotina with the AMF.These findings prompt enquiry into the fundamental ecology of FRE and AMF. We sampled FRE and AMF in roots of Trifolium subterraneum from 58 sites across temperate southern Australia. We investigated the environmental drivers of composition, richness, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 51 publications
5
39
1
Order By: Relevance
“…Understanding the role of microbiota in adaptive plant robustness is important for crop improvement and developing innovative tools that could allow more efficient plant selection (Arnholdt-Schmitt et al, 2014;Arnholdt-Schmitt et al, 2015Nogales et al, 2015). Research on the relevance of endophytic and associated microbiota and usage of microbes as bioinoculants are often hampered by low reproducibility, due to a lack of better understanding of fundamental principles of the plant-microbe interactions (Arnholdt-Schmitt, 2008;Vicente and Arnholdt-Schmitt, 2008;Campos et al, 2015;Mercy et al, 2015Mercy et al, , 2017Bedini et al, 2018;Albornoz et al, 2020) emphasized the need to study mycorrhizal benefits on a case-by-case basis which should consider more holistic and context-dependent views on mycorrhiza functioning at plant family and biomewide levels. Also, it is widely confirmed that endophyte effects are genotype-specific (Abdelrazek et al, 2020a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the role of microbiota in adaptive plant robustness is important for crop improvement and developing innovative tools that could allow more efficient plant selection (Arnholdt-Schmitt et al, 2014;Arnholdt-Schmitt et al, 2015Nogales et al, 2015). Research on the relevance of endophytic and associated microbiota and usage of microbes as bioinoculants are often hampered by low reproducibility, due to a lack of better understanding of fundamental principles of the plant-microbe interactions (Arnholdt-Schmitt, 2008;Vicente and Arnholdt-Schmitt, 2008;Campos et al, 2015;Mercy et al, 2015Mercy et al, , 2017Bedini et al, 2018;Albornoz et al, 2020) emphasized the need to study mycorrhizal benefits on a case-by-case basis which should consider more holistic and context-dependent views on mycorrhiza functioning at plant family and biomewide levels. Also, it is widely confirmed that endophyte effects are genotype-specific (Abdelrazek et al, 2020a,b).…”
Section: Introductionmentioning
confidence: 99%
“…That said, a global study by St€ urmer et al (2018) showed that diversity of G-AMF increased with proximity to tropical biomes, while P€ artel et al (2017) showed diversity of G-AMF decreased with proximity to human disturbance. The handful of studies on M-AMF suggest their diversity and abundance can be promoted by lower temperatures (Albornoz et al, 2020), agricultural land-use (Orchard et al, 2017b), or presence of exotic plant species (Hilbig & Allen, 2015). Furthermore, a global study of native ecosystems showed Mucoromycotina (including M-AMF) were more diverse in the tundra biome while their abundance was lowest in the tropical dry forest biome (Tedersoo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a global study of native ecosystems showed Mucoromycotina (including M-AMF) were more diverse in the tundra biome while their abundance was lowest in the tropical dry forest biome (Tedersoo et al, 2014). Albornoz et al (2020) showed contrasting responses of M-and G-AMF to temperature and edaphic conditions across southern Australia, with higher temperatures and soil pH decreasing richness of M-AMF but increasing richness of G-AMF. However, this study was limited to a single exotic pasture legume species within temperate pastures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the relevance of endophytic and associated microbiota and usage of microbiota inoculation are often hampered by low reproducibility, which is due to a lack of better understanding the fundamental principles of functional plant-microbiota interaction (Arnholdt-Schmitt, 2008, Vicente and Arnholdt-Schmitt, 2008, Mercy et al, 2015, Campos et al, 2015, Mercy et al, 2017, Bedini et al, 2018). Albornoz et al (2020) emphasizes the need for studying mycorrhizal benefits on a case-by-case basis that should consider more holistic and context-dependent views on mycorrhiza functioning at plant family- and biome-wide levels. Also, it is widely confirmed that endophyte effects are genotype-specific (Abdelrazek et al, 2020a,b).…”
Section: Introductionmentioning
confidence: 99%